Hantavirus Cardiopulmonary Syndrome Due to Imported Andes Hantavirus Infection in Switzerland: A Multidisciplinary Challenge, Two Cases and a Literature Review. (22nd May 2018) - Kuenzli, Andrea B; Marschall, Jonas; Schefold, Joerg C; Schafer, Margaret; Engler, Oliver B; Ackermann-Gäumann, Rahel; Reineke, David C; Suter-Riniker, Franziska; Staehelin, Cornelia
Abstract : These 2 cases of Andes hantavirus infection imported to Switzerland illustrate the challenges for intensive care physicians facing severe hantavirus cardiopulmonary syndrome and for the infection control and laboratory teams that deal with an unfamiliar and potentially human-to-human transmissible pathogen. Abstract: Two travellers returning from South America were diagnosed with Andes hantavirus infection, the only member of the Hantaviridae family known to be transmitted from person to person. We describe the clinical course and therapeutic and infection control measures. While both patients showed high viral load (VL) and shedding over several months, 1 patient recovered within 1 week from severe respiratory illness that required noninvasive ventilation, whereas the second patient developed severe hantavirus cardiopulmonary syndrome that required extracorporeal membrane oxygenation for 27 days. The clinical course in the latter patient was complicated by severe disseminated intravascular coagulopathy with diffuse hemorrhage that necessitated mass transfusions, as well as by multiple organ failure, including the need for renal replacement therapy. Results of VL in blood, respiratory secretions, and semen for the first 9 months of follow-up are reported. To our knowledge, these are the first cases of Andes hantavirus infection detected in Europe.